Kolaborasi Mitra Co-branding Dalam Meningkatkan Brand Equity Wonderful Indonesia - Usman, Ernawati; Pramezwary, Amelda (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2023)
Wonderful Indonesia is currently ranked 32nd in the world tourism brand. This position is considered not optimal depend on the potential and possibility of collaboration in tourism marketing. This position under Malaysia, Thailand and Singapore. One of the main programs for increasing brand equity is co-branding. The co-branding program is a collaboration of various brands to support Wonderful Indonesia's brand equity through various joint activities. There are 120 co-branding partners, three partners were selected, tiket.com, Hydrococo and Genpi as partners who won awards as the best collaborative brand 2022. Brand partner collaboration is important to provide media value, increase awareness and brand equity. This research is expected to be able to find patterns of collaboration to optimize the co-branding program and further improve the performance and position of Wonderful Indonesia. This research method is descriptive qualitative, data obtained by in-depth interviews with informants who were determined by purposive sampling with key informants Director of Marketing Communications Ministry of Tourism and Creative Economy. This research shows several models of partner collaboration, collaboration with the Ministry of Tourism and independent collaboration between partners. Some of the determining factors for the value of collaboration are the form of activity, creativity of collaboration, the strength of media tolls, networks, media value generated by partners and the reach of activities carried out. Collaboration activities produces media value that increases PR and brand value through the inclusion of the Wonderful Indonesia logo on products and promotional materials. Several partners released limited edition products collaboration with Wonderful Indonesia with creative tourism themes. The inclusion of the Wonderful Indonesia keywords and logo became the main points of the communication campaign to increase awareness and brand equity.